Measuring multidimensional poverty in India : a new proposal - Alkire, S; Seth, S (Oxford Poverty & Human Development Initiative (OPHI), 2008)
This paper focuses on the methodology by which India’s 2002 Below the Poverty Line (BPL) census data identify the poor and construct a BPL headcount. Using the BPL 2002 methodology and NFHS (National Family Health Survey) data, it identifies which rural families would have been considered BPL were NFHS (National Family Health Survey) data used. It compares these to poor families that would be identified using the same variables with the Alkire Foster multidimensional poverty methodology. It finds that up to 12 per cent of the poor sample population and 33 per cent of the extreme poor could be misclassified as non-poor by the pseudo-BPL method. The paper also develops a sample Index of Deprivation that responds to criticisms regarding BPL data. We compare these results with income poverty and with pseudo-BPL status for sample respondents and disaggregate the index by state and break it down by dimension.